PENDEKATAN PARTISIPATIF DALAM PEMBANGUNAN DI DESA TAWAANG KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - SANGIAN, DANIEL; DENGO, SALMIN; POMBENGI, JERICHO (Sam Ratulangi University, 2018)
Abstract: The purpose of this research is to know how participatory approach in rural development in TawaangVillage, Tenga District, South Minahasa Regency.This research uses descriptive-qualitative approach method. Participatory approaches are seen at all stages ofvillage development from planning, program implementation, monitoring, and program evaluation. Theresearch informants are head dea, head of BPD, head of LPM, community leaders/leaders, and villagers ofTawaang; a total of 8 informants. Data was collected using interview guidelines, while the analysis techniqueused was interactive model analysis from Miles and Hubernann.Based on the results of data analysis, the conclusions are drawn: (1) Participation approach in the planningstage of village development has been done quite well through village musrembang. (2) Participatoryapproaches in program implementation are better quality than at other stages. (3) The implementation ofparticipatory approach in monitoring program implementation is good enough. (4) The evaluation phase of theprogram has also adopted a fairly good participatory approach.Based on the results of the research, several suggestions may be put forward: (1) All representatives ofcommunity groups should be included in the village musrembang. (2) Villagers, especially community leadersand representatives of community groups should be included in the design of program implementation. (3)Community findings of monitoring / monitoring results should be taken seriously by the village government.(4) The village development program evaluation meeting should involve all components of the villagecommunity.Keywords : Participatory Approach, Rural Development.